KONTRIBUSI SAYYID ALAWI AL MALIKI DALAM PERKEMBANGAN ULUMUL HADIS (STUDI ANALISIS KITAB QOWAIDU ASASIYAH FI ILMI MUSTHALAH HADIS) - Muhammad Muhammad; Agusman Damanik; Risna Azahari Pohan (UIN Sumatera Utara Medan, 2021)
This study aims: to find out the figure of the Ulama who studies Ulumul Hadith, let us imitate his character in living his own life as well as the people and their spirit of self-sacrifice. And teach us how to apply the teachings of Hadith and the Qur'an in our lives and glorify them and teach them in our lives. The results of this study indicate that Sayyid Alawi Al Maliki is a cleric figure who was born in the city of Mecca, he is a figure of a very pious scholar and always adorns himself with noble character, he has a big role in da'wah and Islamic education.